2017
DOI: 10.1111/age.12572
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis identifies the genetic basis of fat deposition in the tails of sheep (Ovis aries)

Abstract: SummaryFat-tailed sheep (Ovis aries) can survive in harsh environments and satisfy human's intake of dietary fat. However, the animals require more feed, which increases the cost of farming. Thus, most farmers currently prefer thin-tailed, short-tailed or docked sheep. To date, the molecular mechanism of the formation of fat tails in sheep has not been completely elucidated. Here, we conducted a genome-wide association study using phenotypes and genotypes (the Ovine Infinium HD SNP BeadChip genotype data) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 51 publications
3
59
0
1
Order By: Relevance
“…We performed the GWAS using a two‐step approach via the general linear model and genome‐wide efficient mixed‐model analysis (GEMMA) as detailed by Xu et al . (). The first seven principal components from a multi‐dimensional scaling analysis were used as covariates to account for the biases caused by the population stratification in the GWAS (Xu et al .…”
Section: Genome‐wide and Chromosome‐wise Significant Snps Associated mentioning
confidence: 97%
“…We performed the GWAS using a two‐step approach via the general linear model and genome‐wide efficient mixed‐model analysis (GEMMA) as detailed by Xu et al . (). The first seven principal components from a multi‐dimensional scaling analysis were used as covariates to account for the biases caused by the population stratification in the GWAS (Xu et al .…”
Section: Genome‐wide and Chromosome‐wise Significant Snps Associated mentioning
confidence: 97%
“…More recently, a set of functional genes ( CREB1 , STEAP4 , CTBP1 and RIP140 ) and the candidate genomic region OARX 88–89 Mb, detected using a GWAS and an X‐chromosomal‐wide association study, were also reported to be significantly associated with fat deposition in sheep tails (Xu et al . ). Additionally, Kang et al .…”
Section: Number Of Snps Identified From Three Sheep Breeds Using Rna‐mentioning
confidence: 97%
“…The results of this study also show that some SNPs are within the cAMP responsive element binding protein 1 gene ( CREB1 ), which is associated with lipid metabolism or adipocyte development in mammals (Xu et al . ). Moreover, there are no SNPs located within the HOX and HOX‐related genes ( HOXA6 , HOXA9 , HOXA10 , HOXB2 , HOXB5 , HOXB7 , HOXC4 , HOXC6 , HOXC8 , HOXC9 , HOXC10 , HOXC11 , HOXC12 and HOXC13 ), which are differentially expressed between subcutaneous‐, visceral‐ and tail‐fat tissues (Kang et al .…”
Section: Number Of Snps Identified From Three Sheep Breeds Using Rna‐mentioning
confidence: 97%
“…Among these, fat-tail are an important class of sheep breeds and represent about 25% of the world’s sheep population [3] mainly distributed in the Middle East, North and East Africa and Central Asia. According to Xu et al [4] fat tails represent the energy reserve necessary to survive critical conditions such as drought seasons and food shortage. This statement being emphasized by Mwacharo et al [5] who confirmed that the fat-tails are the predominant sheep across the deserts of northern Africa, and in the highlands, semi-arid and arid environments of eastern and southern Africa while the thin-tails occur in Sudan and in the sub-humid and humid regions of West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…All authors used, for their comparisons, sheep of the same geographic regions to prevent referring to the fat-tail differentiation signals arising from different origins or isolation by distance. These studies included indigenous Chinese [4,8,10,11], Mediterranean-North African [9,12], Iranian [3] and Ethiopian breeds [13]. Similarly, in this study, the genomes of fat-tail sheep from different regions of Africa and Eurasia were contrasted with the genomes of thin-tail sheep of the same geographical area.…”
Section: Introductionmentioning
confidence: 99%